Environmental Together With Interspecific Interactions Determine Bryophyte Distribution in a Protected Mire of Northeast China - Ma, Jin-Ze; Chen, Xu; Mallik, Azim; Bu, Zhao-Jun; Zhang, Ming-Ming; Wang, Sheng-Zhong; Sundberg, Sebastian (Frontiers in Earth Science, 2020)
Question What environmental variables and plant-plant interactions affect mire bryophyte distribution and does the surrounding landscape with human disturbance play a role in the mire bryophyte distribution? Location Jinchuan mire, Northeast China. Methods We studied the spatial distribution of bryophytes in 100 1 × 1 m-quadrats in the mire. Spatial variables were simulated by analysis of the distance-based Moran’s eigenvector maps. Variation partitioning analysis was used to reveal the relative contribution of spatial and environmental variables to bryophytes. The relationship between environmental variables and bryophytes were tested by redundancy analysis. We used co-occurrence and niche overlap models to detect interactions among bryophytes. We also studied the influence of the surrounding landscape on the distribution of bryophytes in relation to water chemistry. Results The eight bryophytes occupying part of the mire had both a general distribution trend and a local spatial structure. Over 40% of the total variation in cover among bryophytes could be explained by spatial and environmental variables. In this fraction, the environmental variables explained 29.7% of the variation, of which only 4.5% was not spatially structured. Redundancy analysis showed the contribution of dwarf shrub cover, Na and P to the bryophyte distribution was relatively large. Concentration of Na and dwarf shrub cover decreased gradually from north to south, and contributed most to the variation in species composition along the first axis. The concentrations of P decreased from east to west, and contributed along the second axis. All the bryophyte species were spatially isolated but with large niche overlaps, indicating that the bryophyte community was structured by interspecific competition. Conclusions Sodium mainly originating from the volcanic hill and P from the paddy fields were the main environmental factors affecting the bryophyte distribution. Concentrations of Na and P showed spatial structure, and resulted in induced spatial dependence playing a major role in the spatial structure of the bryophyte community. Dwarf shrubs affected by nutrient distribution in the mire significantly influenced the bryophyte distribution in the mire. We conclude that the surrounding ecosystems had important influence on bryophyte distribution via nutrient influx. Furthermore, competitive interactions exacerbated the spatial separation of bryophytes.